Interaction effects of degradable nitrogen sources and straw treatment on rumen parameters and microbial protein synthesis in sheep - GHASEMI, E; KHORVASH, M; GHORBANI, G R; HASHEMZADEH, F; SAEBI-FAR, M; KAHYANI, A; KAZEMI-BONCHENARI, M (The Indian Journal of Animal Sciences, 2014)
In this study, the effects of 2 rumen degradable nitrogen, N, source (urea vs. casein) were investigated on rumen degradability, ammonia concentration, dilution rate, microbial protein synthesis (MPS) and MPS efficiency (EMPS) in sheep fed diet based on untreated straw (US) or treated straw (TS). Four rumen fistulated sheep were assigned to 1 of the 4 treatments: (i) US with urea (USU); (ii) US with casein (USC); (iii) TS with urea (TSU); and (iv) TS with casein (TSC), according to a 4 × 4 Latin square design. Barley straw was treated with 4.1% sodium hydroxide (w/ w DM basis; pH 11.5) followed by 2% hydrogen peroxide. The treated straw was packed in 220 l drums and kept for 6 weeks. Compared to US diets, feeding the TS diets enhanced ruminal fiber degradability (62.3 vs 46.3%), total tract organic matter (OM) digestibility (59.4 vs 53.8%), OM intake (768 vs 546 g/d), dilution rate (0.082 vs 0.056/h), and MPS (45.7 vs 29.7 g/d), but it had no effect on EMPS. Rumen fiber degradability but not the DM one of only TS enhanced with casein supplementation as compared to urea supplementation. No interaction was found between supplemented nitrogen sources and straw type. It is concluded that substitution of US with TS increased intake, digestibility and MPS when supplemented with either urea or casein as nitrogen source. However, fiber degradability was improved with casein supplementation.